Legal design for establishing a novel parastatal public health institute – Japan Institute for Health Security: A case study - Miyako Otsuka; Mio Kato; Takaji Wakita; Tomoya Saito (PLOS Global Public Health, 2026)
The COVID-19 pandemic exposed critical gaps in Japan’s infectious disease governance, including fragmented structures and limited coordination between research and policy. In response, Japan established the Japan Institute for Health Security (JIHS) in April 2025 by merging the National Institute of Infectious Diseases and the National Center for Global Health and Medicine, yet no comprehensive assessment exists of the legal frameworks supporting this transformation. This descriptive qualitative study combined document review with semi-structured key informant interviews to examine JIHS governance structures, objectives, and legal reforms. We reviewed five pieces of legislation, two grey literature documents, and eight government publications, and interviewed eight purposively selected informants—one national legislator, four senior Ministry of Health, Labour and Welfare officials, and three JIHS executive officers—in Japanese between August and September 2025, analyzing transcripts with Braun and Clarke’s thematic analysis framework. The JIHS Act and associated amendments established JIHS as a Special Public Corporation, creating mechanisms for vertical and horizontal coordination and embedding preparedness and research capacity as core elements of national health security. Consistent with Japanese enabling legislation, the Act sets a broad framework whose operational adequacy is calibrated through subordinate regulations and administrative practice. Document analysis and interviews revealed a tripartite governance model integrating political leadership, administrative coordination, and scientific expertise, and informants emphasized that inter-agency trust and cultural integration between the merged institutions are essential for effective implementation. JIHS thus internalizes scientific advice within the national public health framework while preserving institutional autonomy, offering context-dependent lessons that underscore the importance of tailoring reforms to national administrative traditions. Future evaluation will focus on the real-world operationalization of this enacted framework, assessing whether its specific design choices translate into improved pandemic preparedness and response.